Real world evidence of Lenvatinib + anti PD-1 as an advanced line for metastatic melanoma - Stoff, Ronen; Asher, Nethanel; Laks, Shachar; Steinberg, Yael; Schachter, Jacob; Shapira-Frommer, Ronnie; Grynberg, Shirly; Ben-Betzalel, Guy (Frontiers in Oncology, 2023)
Introduction Immunotherapy has revolutionized the prognosis of patients with metastatic melanoma. To date, the most active regimen is the combination of ipilimumab + nivolumab (ipi-nivo) achieving a response rate of nearly 60% and a median survival (OS) of 6 years. However, approximately 40% of patients experience primary resistance, while around 50% experience secondary resistance, highlighting the need for an effective second-line treatment option. The recently published results on the use of lenvatinib + pembrolizumab in the advanced line setting led to the adoption of this regimen at our institution. Here we present our experience with this regimen, focusing on efficacy and safety. Methods Electronic medical records of patients treated at a tertiary referral melanoma center, with at least one cycle of anti PD-1 + lenvatinib from 2020 to 2023 were analyzed for baseline demographic characteristics, disease related characteristics and treatment outcomes. Results Forty-two patients were identified. The Response rate (RR) was 28% and the disease control rate was 38%. Responses were seen across different melanoma subtypes, including 67% in acral melanoma, 20% in uveal melanoma, and 25% in mucosal melanoma. Patients with a more aggressive disease manifested by elevated lactate dehydrogenase (LDH) achieved a RR of 26%, while patients with active central nervous system (CNS) metastases had a RR of 31%, and an intra-cranial RR of 23%. Responses were seen across lines of treatment, with a 25% RR in the second and third lines, and a 36% RR in the fourth and fifth lines. The median progression free survival was 3 months, and the median survival was 11 months. The treatment was not easily tolerated with 31% of the patients experiencing grade 3-4 toxicity, which was manageable through dose interruptions and reductions. Only 7% of patients discontinued the treatment due to toxicity. Conclusion Lenvatinib in combination with anti-PD1 had demonstrated both relative safety and efficacy in patients with metastatic melanoma of all subtypes in the advanced line setting. We are eagerly anticipating the mature results of the LEAP-004 study hoping that this regimen will receive regulatory approval, paving the way for its widespread adoption in daily practice worldwide